2021
DOI: 10.21608/edj.2021.55094.1425
|View full text |Cite
|
Sign up to set email alerts
|

Locator versus stress free implant bar attachments for two -implants immediately loaded by mandibular overdentures. A one year randomized study

Abstract: Aim:The purpose of this short-term randomized trial was to study clinical and radiographic outcomes of Locators and stress free implant SFI bar attachments used for two -implants immediately loaded by mandibular overdentures. Material and method:Twelve edentulous participants (6 males and 6 females) received new maxillary and mandibular dentures and wore them for 3 months to increase muscular control. Two fixtures were installed in the canine regions of the mandible and immediately loaded by mandibular overden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…(25) Several studies also reported that the increased plaque scores with bar attachment may be related to the relieving spaces around the bar and the abutments which lead to gingival hyperplasia that may permit the rotation of overdentures around the bar without implant loading but help plaque to accumulate . (26)(27)(28)(29)(30) Although implant pocket depth increased with time, this increase was not significant. Also, no significant difference in pocket depth between groups was observed.…”
Section: Discussionmentioning
confidence: 96%
“…(25) Several studies also reported that the increased plaque scores with bar attachment may be related to the relieving spaces around the bar and the abutments which lead to gingival hyperplasia that may permit the rotation of overdentures around the bar without implant loading but help plaque to accumulate . (26)(27)(28)(29)(30) Although implant pocket depth increased with time, this increase was not significant. Also, no significant difference in pocket depth between groups was observed.…”
Section: Discussionmentioning
confidence: 96%
“…Las sobredentaduras en el maxilar inferior retenidas por dos implantes colocados en la región interforaminal han sido bien documentadas en investigaciones clínicas y se han sugerido como tratamiento estándar para el paciente desdentado 20 . Ahora bien, es en la rehabilitación del maxilar superior edéntulo con implantes, donde se vislumbran las mayores controversias referidas a esta temática.…”
Section: Las Sobredentaduras Inferiores Y La Evidencia Disponible Como Primera Alternativa Ideal De Tratamiento En La Mandíbula Edéntulaunclassified